Redox Mediator with the Function of Intramolecularly Disproportionating Superoxide Intermediate Enabled High‐Performance Li–O2 Batteries. Issue 12 (17th January 2022) - Sun, Zongqiang; Lin, Xiaodong; Dou, Wenjie; Tan, Yanyan; Hu, Ajuan; Hou, Qing; Yuan, Ruming; Zheng, Mingsen; Dong, Quanfeng
Abstract: The large charge overpotential and poor cycling stability triggered by sluggish Li2 O2 oxidation kinetics and severe superoxide‐related side reactions greatly restrict the development and application of lithium–oxygen batteries. Finding out high‐efficiency catalysts that can effectively facilitate a highly reversible formation/decomposition of lithium peroxide is still a crucial challenge in the field of Li–O2 batteries. Herein, a soluble catalyst of 2, 2'‐Azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic acid) diammonium salt (ABTS) that can promote highly reversible formation and decomposition of Li2 O2 during discharge and charge processes is reported for the first time. During discharge, it can capture and couple two LiO2 intermediates via its sulfonate and ammonium ions, and induce the intramolecular disproportionation reaction to produce Li2 O2 through ionic microenvironment, which not only prompts the solution‐phase growth of Li2 O2, but also restricts the reactivity of LiO2 intermediate, thus significantly alleviating the electrode surface passivation issue and suppressing the superoxide‐related side reactions. During charge, it can quickly transport electrons between the electrode and Li2 O2 by serving as a new kind of redox mediator (RM), thus greatly facilitating the Li2 O2 oxidation kinetics. As a result, the Li–O2 batteries that incorporate ABTS exhibit outstanding electrochemical performance, low charge overpotential, high discharge capacity, and high cycling stability. Abstract : 2, 2'‐Azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic acid) diammonium salt (ABTS) is employed as a soluble catalyst for Li−O2 batteries. Benefiting from its ability to couple two LiO2 intermediates via its sulfonate and ammonium ions and transport electrons between electrode and Li2 O2, the solution‐phase growth and oxidation kinetics of Li2 O2 can be greatly promoted. Consequently, ABTS‐catalyzed Li−O2 batteries can achieve highly reversible O2 conversion and exhibit good performance.